First evidence of established populations of the taiga tick Ixodes persulcatus (Acari: Ixodidae) in Sweden - Jaenson, Thomas G. T.; Varv, Kairi; Frojdman, Isabella; Jääskeläinen, Anu; Rundgren, Kaj; Versteirt, Veerle; Estrada-Pena, Agustin; Medlock, Jolyon M.; Golovljova, Irina (Parasites & Vectors, 2017)
Background: The tick species Ixodes ricinus and I. persulcatus are of exceptional medical importance in the western and eastern parts, respectively, of the Palaearctic region. In Russia and Finland the range of I. persulcatus has recently increased. In Finland the first records of I. persulcatus are from 2004. The apparent expansion of its range in Finland prompted us to investigate if I. persulcatus also occurs in Sweden. Methods: Dog owners and hunters in the coastal areas of northern Sweden provided information about localities where ticks could be present. In May-August 2015 we used the cloth-dragging method in 36 localities potentially harbouring ticks in the Bothnian Bay area, province Norrbotten (NB) of northern Sweden. Further to the south in the provinces Vasterbotten (VB) and Uppland (UP) eight localities were similarly investigated. Results: Ixodes persulcatus was detected in 9 of 36 field localities in the Bothnian Bay area. Nymphs, adult males and adult females (n = 46 ticks) of I. persulcatus were present mainly in Alnus incana - Sorbus aucuparia - Picea abies - Pinus sylvestris vegetation communities on islands in the Bothnian Bay. Some of these I. persulcatus populations seem to be the most northerly populations so far recorded of this species. Dog owners asserted that their dogs became tick-infested on these islands for the first time 7-8 years ago. Moose (Alces alces), hares (Lepus timidus), domestic dogs (Canis lupus familiaris) and ground-feeding birds are the most likely carriers dispersing I. persulcatus in this area. All ticks (n = 124) from the more southern provinces of VB and UP were identified as I. ricinus. Conclusions: The geographical range of the taiga tick has recently expanded into northern Sweden. Increased information about prophylactic, anti-tick measures should be directed to people living in or visiting the coastal areas and islands of the Baltic Bay. Peer reviewed